Pendampingan Planogram untuk Pemilik Ritel - Qurtubi Qurtubi; Joko Sulistio; Vembri Noor Helia; Melinska Ayu Febrianti; Jundi Nourfateha Elquthb (Universitas Islam Indonesia, 2024)
Retail owners need to utilize transaction data for customer buying patterns. By knowing the pattern of customer purchases, retail owners can adjust the layout of the store and the layout of goods on the display rack or a planogram to increase product visibility which refers to increased sales. Not many retail owners are aware of the benefits of using a good planogram and how to design it, so it is essential to provide training related to planograms to the public so they can know how to create planograms properly and correctly. Community service will be conducted from July to October 2022 in Sleman, Bantul, and Temanggung Regency and its surroundings, with interactive mentoring methods with material delivery and questions and answers. Submission of the material contains definitions, benefits, and illustrations of the application of the planogram in the retail industry, as well as the stages of planning the planogram. With this community service, it is hoped that retail business owners who participate in the mentoring can utilize transaction data at each retailer to develop a planogram based on customer purchasing patterns, thereby increasing sales and customer satisfaction.